DETERMINATION OF PHYSICOCHEMICAL AND GEOMETRICAL PROPERTIES OF SOME CARVEDILOL DEREVITIVES - Hatem, Oraas Adnan; Abed Suhail, Falah Shareef; Mousa Juda, Amer (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Five derivatives of Carvedilol with different activities were studied in order to suggest unprepared derivative of carvedilol and suggestion a general equation to calculate the activity foe any Carvedilol derivative.. Methods: GAUSSIAN 03 software employed to calculate physicochemical and geometrical properties of carvedilol derivatives, the calculated quantum chemical parameters are: The energy gap between the highest occupied molecular orbital and lowest unoccupied molecular orbital (HOMO-LUMO), dipole moment (μ), electronegativity (χ), electron affinity (A), global hardness (η), ionization potential (I), and the global electrophilicity (ω). The resulting properties used in quantitative structure-activity relationship equation to predict activity. Results: Suggested unprepared carvedilol derivative with an activity of 1.99 × 10 mg as well as development of a general equation, two formula for calculate activity of carvedilol derivatives specifically Log 1/C = −29.5744 + 17.1334 Log p + 19603.97 ∆ HOMO-LUMO + 2.7725 μ – 38902 η by mean of physicochemical properties and Log 1/C = 2828.25 + 15.01 N electron density − 308.016 O electron density + 306.97 H electron density + 0.32477 molecular length by mean of geometrical properties. −5 Conclusion: This process may be considered the cost- and time-consuming process, according to the ability of suggestions, new structures to be synthesized using computational chemistry methods. Keywords: Quantitative structure-activity relationship, Density functional theory, Highest occupied molecular orbital and lowest unoccupied molecular orbital gap, Global hardness, Global electrophilicity.